Sex differences in outcomes of first episode psychosis: results from an early intervention service - Domenicano, Ilaria; Onofrio, Alice; Citton, Martina; Vecchioni, Ludovica; De Donatis, Domenico; Bertelli, Raffaella; Emanuelli, Franca; Grassi, Luigi; Ferrara, Maria (Frontiers in Behavioral Neuroscience, 2025)
BackgroundEarly intervention services (EIS) for first-episode psychosis (FEP) play a key role in shaping a better disease trajectory for both affective and non-affective psychosis. Psychotic disorders tend to present sex differences both from an epidemiological and clinical perspective.AimsThe primary aim of this study is to investigate sex-based differences in outcome of patients admitted to EIS for FEP, analysing clinical differences and recovery rates during a 24 months long follow-up.MethodsA longitudinal cohort study was conducted. Patients were those admitted to the EIS in Ferrara between 2012 and February 27th, 2025 who met the following enrolment criteria: (a) diagnosed with affective or non-affective FEP; (b) not being treated for more than 24 months; (c) absence of intellectual disability; (d) aged between 18 and 35 years; (e) absence of organic psychosis. Socio-demographic and clinical characteristics were collected at program admission. The HoNOS (Health of the Nation Outcome Scale) was administered at baseline and every 6 months for the 24 months follow-up to compare sex differences in terms of symptoms severity and clinical recovery (HoNOS total score <8). Outcomes over time were compared between groups using mixed effects models repeated measures analysis of variance (MMRM).ResultsA total of 174 patients were included in the study, most were males (74.1%), and most men vs. women were born in Italy (81.4% vs. 66.7%, p = 0.04). At admission, men had significantly higher rates of cannabis use (56.6% vs. 22.2%), tobacco use (62% vs. 28.9%), and alcohol misuse (51.2% vs. 15.5%) (p < 0.001). Men, compared to women, at 6 and 12 months showed significantly lower clinical severity than women (11.9 vs. 14.5, p = 0.03; 9.4 vs. 11.9, p = 0.05 respectively), and higher probability of being in recovery at 12 months (p = 0.04), indicating a faster clinical improvement. At 24-month, more men than women were NEET (Not in Education, Employment or Training) (26.3% vs. 8%, p = 0.04).ConclusionOverall, our study highlighted significant sex differences both at admission as well as in outcomes. Men tend to improve more rapidly than women, then reaching a plateau with no substantial differences between sexes at 24 months. Further studies should identify sex-specific outcome predictors that could help in early patients’ identification, thus leading to improve clinical trajectories and long-term prognosis.